Review of the distribution of Sapygidae in Italy and new records (Hymenoptera: Vespoidea) - Ceccolini, Filippo; Cianferoni, Fabio (Fragmenta entomologica, 2018)
The distribution of the Italian species of Sapygidae is reviewed and new occurrence records for some species are given. Monosapyga clavicornis (Linnaeus, 1758) is recorded for the first time in Lazio and Abruzzo, Polochrum repandum Spinola, 1806 in Abruzzo, and Sapygina decemguttata (Jurine, 1807) in Veneto. Due to insufficient sampling efforts in Italy, all the Italian species of Sapygidae should be currently considered as Data Deficient (DD) according to the IUCN Red List Categories and Criteria.